Clinical characteristics of people with heart failure in Australian general practice: results from a retrospective cohort study. (28th October 2021) - Sindone, Andrew P.; Haikerwal, Deepak; Audehm, Ralph G.; Neville, Alexander Munro; Lim, Kevin; Parsons, Richard Whaddon; Piazza, Peter; Liew, Danny
Abstract: Aims: Heart failure (HF) causes significant morbidity and mortality, but the rates and characteristics of people with HF in Australia are not well studied. SHAPE set out to describe the characteristics of HF patients seen in the real‐world setting. Methods: We analysed anonymized patient data extracted from the clinical software of 43 participating GP clinics for the 5 year period from 1 July 2013 to 30 June 2018. Patients were stratified into 'definite' and 'probable' HF based on a hierarchy of selection criteria and analysed for their clinical characteristics. Symptoms and signs of HF and ejection fraction data were searched for within the free text of the medical notes. Results: Of the 1.12 million adults seen regularly, 20 219 were classified as having definite or probable HF. The mean age of the population was 69.8 years, 50.6% were female, and mean body mass index was 31.2 kg/m 2 . Fewer than 1 in 6 had the HF diagnosis optimally recorded. Only 3.2% (650 patients) had their left ventricular ejection fraction (EF) quantified: 40.9% had an EF ≥50% and 59.1% had an EF <50%. The most common comorbidities in people with HF were hypertension (41.1%), chronic obstructive pulmonary disease/asthma (25.1%) and depression/anxiety (18.4%). Hypotension (2.3%), bradycardia (6.3%), severe renal impairment (6.4%) and hyperkalaemia (2.0%) were uncommon. Just over one‐third (37.8%) had iron deficiency. Loop diuretic use was common (56.7%) but only 33.7% were on a guideline recommended beta‐blockers. Use of ivabradine (1.4%) and sacubitril/valsartan (1.2%) was very low, while 39.9% had been prescribed an angiotensin‐converting enzyme inhibitor, 31.6% an angiotensin receptor blocker and 16.0% spironolactone. Many patients were prescribed medications that may worsen HF or are relatively contraindicated, such as macrolide antibiotics (29.9%), corticosteroids (25.8%), nonsteroidal anti‐inflammatory drugs (23.9%), and tricyclic antidepressants (9.4%). Conclusions: Heart failure is poorly documented in general practice records and may be contributing to untoward downstream effects, such as low documentation of echocardiography, poor use of guideline recommended therapies and frequent use of medications that may worsen HF.